Biophysical assay for tethered signaling reactions reveals tether-controlled activity for the phosphatase SHP-1 - Goyette, J; Solis Salas, C; Coker-Gordon, N; Bridge, M; Isaacson, S; Allard, J; Dushek, O (American Association for the Advancement of Science: Science Advances, 2017)
Tethered enzymatic reactions are ubiquitous in signalling networks but are poorly understood. Here, a novel mathematical analysis is established for tethered signalling reactions in surface plasmon resonance (SPR). Applying the method to the phosphatase SHP-1 interacting with a phosphorylated tether corresponding to an immune receptor cytoplasmic tail provides 5 biophysical/biochemical constants from a single SPR experiment: two binding rates, two catalytic rates, and a reach parameter. Tether binding increased the activity of SHP-1 by 900-fold through a binding-induced allosteric activation (20-fold) and a more significant increase in local substrate concentration (45-fold). The reach parameter indicates that this local substrate concentration is exquisitely sensitive to receptor clustering. We further show that truncation of the tether leads not only to a lower reach but also to lower binding and catalysis. The work establishes a new framework for studying tethered signalling processes and highlights the tether as a control parameter in clustered receptor signalling.